2011
DOI: 10.1504/ijcbdd.2011.038656
|View full text |Cite
|
Sign up to set email alerts
|

Nascent proteomes of ischemic-injured and ischemic-tolerant neuronal cells

Abstract: In a recent study on ischemic rodent brains, we quantitatively characterised and compared brain proteomes under ischemic-preconditioned or injured or tolerant conditions. We discovered an enriched presence of repressive transcriptional regulator proteins with essential roles as epigenetic regulators in ischemic-tolerant brains (Stapels et al., 2010). We further showed their robust, dynamic and differential changes under different ischemic conditions in brains and in cultured neuronal cells. In the present work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…After incubation, proteins were extracted from individual PBMC preparations and pooled according to study groups as follows: female patients, male patients, female controls, and male controls. The AHA-labeled PBMC proteins (i.e., nascent proteome) were isolated from the total proteome by means of Click reaction 3, 4 as described in SMM.…”
Section: Study Subjects and Methodsmentioning
confidence: 99%
“…After incubation, proteins were extracted from individual PBMC preparations and pooled according to study groups as follows: female patients, male patients, female controls, and male controls. The AHA-labeled PBMC proteins (i.e., nascent proteome) were isolated from the total proteome by means of Click reaction 3, 4 as described in SMM.…”
Section: Study Subjects and Methodsmentioning
confidence: 99%
“…In 2011, we published the first study on nascent proteomes of cultured, ischemic neuronal cells 35. The results support the feasibility.…”
Section: Nascent Proteomics In Stroke Researchmentioning
confidence: 67%
“…To get insight into pathophysiological changes in the ischemic penumbra, it is desirable to investigate its translational changes. With quantitative proteomic analysis, we detected 3,837 proteins qualified with high confidence ( Supplementary Table S5), which is much larger than previous cell-based studies in which 524-1081 proteins were identified under OGD treatments (Jin et al, 2004;Datta et al, 2009;Zhou et al, 2011;Herrmann et al, 2013). Importantly, 427 and 398 proteins in our study had their abundance changed ≥1.4-fold (p < 0.05) between H−G or H+LG and N+G treatments, respectively, and 105 proteins had their abundance difference ≥1.5-fold between H−G and H+LG treated cells.…”
Section: Discussionmentioning
confidence: 77%